Problematika Pembentukan Karakter Religius Siswa Pada Pembelajaran PAI di SMP Negeri 1 Sei Kepayang Timur - Mazid, Miftah Ilham; Nurmawati, Nurmawati (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2024)
Abstract: This study highlights the importance of developing students' religious character to create a generation that is moral, ethical, and highly principled. In the era of globalization, religious values are often neglected, making schools play a crucial role in supporting the development of students' religious character. This study employs a qualitative method to explore the experiences, views, and interpretations of students, teachers, and parents regarding the process of forming religious character. The purpose of this study is to identify and analyze the factors that hinder the development of students' religious character in schools and to seek effective solutions to overcome these obstacles. Data were collected through in-depth interviews, observations, and document analysis. The research findings revealed several significant challenges, such as the lack of parental attention to their children's religious education, inadequate school facilities, and a shortage of professional teachers who can effectively guide students in religious aspects. These challenges require immediate attention and action. Therefore, schools need to collaborate with parents to raise awareness of the importance of religious education, improve school facilities, and recruit and train competent teachers in religious education. Government support in the form of policies and funding is also crucial to ensure the effective development of students' religious character. Keywords: religious character formation, religious education, school-parent collaboration Abstrak: Penelitian ini menyoroti pentingnya pembentukan karakter religius siswa dalam menciptakan generasi yang bermoral, beretika, dan berintegritas tinggi. Di era globalisasi, nilai-nilai religius sering kali terabaikan, sehingga sekolah memiliki peran penting dalam mendukung perkembangan karakter religius siswa. Penelitian ini menggunakan metode kualitatif untuk menggali pengalaman, pandangan, dan interpretasi siswa, guru, serta orang tua terkait proses pembentukan karakter religius. Tujuan penelitian ini adalah untuk mengidentifikasi dan menganalisis faktor-faktor penghambat dalam pembentukan karakter religius siswa di sekolah, serta mencari solusi yang tepat untuk mengatasi hambatan tersebut. Data dikumpulkan melalui wawancara mendalam, observasi, dan analisis dokumen. Hasil penelitian mengungkapkan beberapa kendala utama, seperti kurangnya perhatian orang tua terhadap pendidikan agama anak-anak, fasilitas sekolah yang belum memadai, dan keterbatasan jumlah guru profesional yang mampu membimbing siswa dalam aspek keagamaan. Kendala-kendala ini memerlukan perhatian dan tindakan segera. Oleh karena itu, sekolah perlu bekerja sama dengan orang tua untuk meningkatkan kesadaran akan pentingnya pendidikan agama, memperbaiki fasilitas sekolah, serta merekrut dan melatih guru yang kompeten di bidang keagamaan. Dukungan dari pemerintah dalam bentuk kebijakan dan pendanaan juga sangat dibutuhkan untuk memastikan pembentukan karakter religius siswa berjalan dengan efektif. Kata kunci: pembentukan karakter religius, pendidikan agama, kolaborasi sekolah-orangtua